Pelaksanaan Digitalisasi Usaha Untuk Pertumbuhan Dan Pengembangan UMKM Daerah Bersama PT. Narasumber Teknologi Indonesia - Muhammad Alfan Fitroni; Acep Samsudin (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
PT. Narasumber Teknologi Indonesia is a company that focuses on cooperative computerized accounting training, technical guidance for the implementation of technology for small and medium-sized enterprises (SMEs), national cooperative software training, sharia supervisory board for cooperatives, computerized management training for cooperatives and SMEs, as well as the digitalization of Micro, Small, and Medium Enterprises (MSMEs). Additionally, PT. Narasumber Teknologi Indonesia serves as a platform for the younger generation to develop their potential as agents of business digitization through the final project of the program activities. This involves providing training and mentoring to local MSMEs as an effort to digitize their businesses and help solve the problems that hinder or constrain the development of local MSMEs. This research provides insights for local business practitioners to implement digitization in their businesses in order to achieve sustainable growth and success for MSMEs in the ever-evolving digital era. The implementation of training and mentoring for local MSMEs is expected to help them Go Digital, improving efficiency and productivity, enhancing product quality and services, and increasing market access for local MSMEs.